Molecular characterization of digestive proteases of the yellow mealworm, Tenebrio molitor L. - Prabhakar, Sheila (Kansas State University, 2006)
Coleopteran insects compensate for dietary protease inhibitors by a number of mechanisms. To study this compensation response at the molecular level, the digestive proteases of Tenebrio molitor were studied. Biochemical studies of the pH optima and inhibitor sensitivity of proteases indicated the cysteine proteases were mostly in the anterior and serine proteases were in the posterior midgut of T. molitor larvae. Expressed Sequence Tags (ESTs) from T. molitor larval midgut cDNA libraries contained sequences encoding putative digestive proteases. Of a total of 1,528 cDNA sequences, 92 cDNAs encoded proteases, and 50 full-length cDNAs were grouped into serine, cysteine and metallo protease classes. Sequences tmt1a, tmt1b and tmt1c were identified as genes encoding isoforms of T. molitor trypsin, and tmc1a encoded T. molitor chymotrypsin. The general distribution cysteine protease transcripts in the anterior and serine protease transcripts in the posterior midgut, of T. molitor larvae, was in agreement with the biochemically-characterized compartmentalization of proteases. Expression analyses of selected transcripts demonstrated varied expression patterns across five developmental stages of T. molitor, with maximal expression of most protease transcripts in first instar larvae. Dietary serine and cysteine protease inhibitors fed in combination to early-instar T. molitor larvae caused a significant delay in larval growth in 21-day-old larvae. Real-time quantitative PCR analysis of RNA isolated from larvae fed different protease inhibitor treatments indicated that dietary inhibitors affected the expression of serine and cysteine proteases. Larvae fed soybean trypsin inhibitor, a serine protease inhibitor, compensated by the hyperproduction of proteases from the same class, as well as the upregulation of cysteine proteases. A cysteine protease inhibitor, E-64, caused a reduction in the hyperproduction of all proteases, and, in combination with the soybean trypsin inhibitor, lowered the compensation response of T. molitor larvae to negligible levels. These data suggest that T. molitor larvae are more sensitive to the effects of cysteine protease inhibitors, perhaps because these proteases are the first line of defense for larvae against plant protease inhibitor. The bioassay and molecular studies suggested that combinations of inhibitors that target both serine and cysteine proteases are needed to effectively control larval infestations of T. molitor.
Keywords: Yellow Mealworm; Digestive proteases; Expressed Sequence Tag (EST); Compensation response to protease inhibitors; Biology, Entomology (0353)